Preventive effectiveness of varicella vaccine in healthy unexposed patients - María Catalina Castro; Pamela Rojas (Medwave, 2020)
INTRODUCTION Chickenpox is an infectious disease caused by varicella-zoster virus. Varicella vaccine is conventionally used for its prevention, and its administration seeks to reduce the onset of the disease and complications associated. However, there is still controversy about its effectiveness.